Jak wyglądały lasy pierwotne Europy pod presją dużych roślinożerców? - Borkowski, Jakub (Leśne Prace Badawcze, 2011)
The long-standing received wisdom has been that primeval forests (before the development of agriculture) in temperate Europe were created by broad-leaved trees forming closed-canopies. However, a recent theory has challenged this perception by proposing that primeval forests were in fact wood pastures: a mosaic of grassland and forest patches. These forest patches were created mainly by oak and hazel. Grazing by large herbivores, mostly aurochs and tarpan, living at high densities, later replaced by cattle and horses in the agricultural epoc, allowed wood-pasture formation. The regeneration of trees in such conditions was possible thanks to the protective shelter offered by thorny shrubs. Several forest reserves created in Europe, serving as references for primeval forests, have been succeeding without pressure from large herbivores and therefore their character may be different than that of real primeval vegetation. Although some palaeoecological studies suggest that primeval forests had closed-canopies, other analyses indicate that closed canopy forests were interrupted by a remarkably large proportion of more open areas. It is hard to judge what was the true character of primeval forests, but the role of large herbivores in shaping primeval forest structure has been neglected. It is believed that there was a higher proportion of mega-herbivorous mammals in the temperate zone during the late Pleistocene than the proportion presently living in Africa. Given the evidence that large herbivores can effectively determine the openness of African landscapes, their potential to have shaped temperate primeval forests should not be under-estimated.